Facile Synthesis of Dispiroheterocycles through One-Pot [3+2] Cycloaddition, and Their Antiviral Activity - Zhang, Min; Yang, Wenbo; Li, Kailu; Sun, Ke; Ding, Jianfen; Yang, Liuqing; Zhu, Chunyin (Synthesis, 2019)
A facile synthesis of novel dispiroheterocycles has been developed through one-pot [3+2] cycloaddition between isatins, amino acids, and aurones. Thirty different dispiroheterocycles were synthesized eusing this method which features mild conditions, convenient operation, and high efficacy. Evaluation of the bioactivity of these dispiroheterocyclic products revealed antiviral activity against tobacco mosaic virus (TMV).
Keywords: cycloaddition; isatins; aurones; dispiroheterocycles; antiviral activity